Volatile Organic Constituents of Clinopodium gilliesii (Benth.) Kuntze: Analysis by HS-SPME and classic hydrodistillation - Vázquez, Ana María; Aimar, Mario Leandro; Decarlini, María Florencia; Demmel, Gabriela Ines; Cantero, Juan Jose; Ruiz, Gustavo Miguel (Revista Colombiana de Investigaciones Agroindustriales, 2016)
In the present research, an analytical methodology to micro scale based on the use of the HS-SPME/GC-MS to determine volatile compounds present in Clinopodium gilliesii (Benth.) Kuntze (Lamiaceae) was employed, and settled differences and similarities with its essential oil obtained by hydrodistillation. A systematic description of the volatile components of flowers, stems, leaves and combined aerial parts (whole plant) was constructed via GC-MS analyses of HS-SPME adsorbed compounds and of essential oils obtained through hydrodistillation of the same tissues. Piperitenone oxide and piperitone oxide were the main components of both the HS-SPME analysis and essential oil analysis. The HS-SPME method can achieve comparable results to those obtained by essential oil analysis, by using very fewer samples, a shorter extraction time and a much simpler procedure. Para citar este artículo Vázquez, A., Aimar, M.,Decarlini, M., Demmel, G., Cantero, J y Ruiz, G. (2016). Volatile Organic Constituents of Clinopodium gilliesii (Benth.) Kuntze: Analysis by HS-SPME and classic hydrodistillation. Rev. Colomb. Investig. Agroindustriales, 3(1), 91-100. DOI: http://dx.doi.org/10.23850/24220582.351